EXPLANATION:
Let the smaller no. be x.
Therefore, The bigger no. = x+12
x + 12 + x = 84
=> 2x = 84-12
=> x = 72/2
=> x = 36
ANSWER: The two numbers are (36+12) 48 & 36
Hope it helps u!
Answer:
2^8x-3
Step-by-step explanation:
Answer:
Linda would have to babysit for 9 hours.
Step-by-step explanation:
26+54=80
54÷6=9
Answer:
170℅×16
=27.2
hope it helps you
make me brainliest...... :)
Answer:
![P(x) = x^3 - 10x^2+ 34x-40](https://tex.z-dn.net/?f=P%28x%29%20%3D%20x%5E3%20-%2010x%5E2%2B%2034x-40)
Step-by-step explanation:
Given
-- Leading coefficient
![Zeros: 4\ and\ 3 - i](https://tex.z-dn.net/?f=Zeros%3A%204%5C%20and%5C%203%20%20-%20i)
Required
Determine the polynomial
Represent the zeros with a and b
Such that
![a = 4](https://tex.z-dn.net/?f=a%20%3D%204)
![b = 3 - i](https://tex.z-dn.net/?f=b%20%3D%203%20-%20i)
The polynomial is:
![P(x) = p * (x - a) * (x - b)](https://tex.z-dn.net/?f=P%28x%29%20%3D%20p%20%2A%20%28x%20-%20a%29%20%2A%20%28x%20-%20b%29)
![P(x) = 1 * (x - 4) * (x - (3 - i))](https://tex.z-dn.net/?f=P%28x%29%20%3D%201%20%2A%20%28x%20-%204%29%20%2A%20%28x%20-%20%283%20-%20i%29%29)
However, to solve further: We need to symmetrise over 3-i and its conjugate
![P(x) = 1 * (x - 4) * (x - (3 - i))* (x - (3 + i))](https://tex.z-dn.net/?f=P%28x%29%20%3D%201%20%2A%20%28x%20-%204%29%20%2A%20%28x%20-%20%283%20-%20i%29%29%2A%20%28x%20-%20%283%20%2B%20i%29%29)
![P(x) = (x - 4) * (x - (3 - i))* (x - (3 + i))\\\\](https://tex.z-dn.net/?f=P%28x%29%20%3D%20%20%28x%20-%204%29%20%2A%20%28x%20-%20%283%20-%20i%29%29%2A%20%28x%20-%20%283%20%2B%20i%29%29%5C%5C%5C%5C)
To define a suitable function, the expression becomes
![P(x) = (x - 4) * ((x - 3)^2+1)](https://tex.z-dn.net/?f=P%28x%29%20%3D%20%20%28x%20-%204%29%20%2A%20%28%28x%20-%203%29%5E2%2B1%29)
![P(x) = (x - 4) * ((x - 3)(x - 3)+1)](https://tex.z-dn.net/?f=P%28x%29%20%3D%20%20%28x%20-%204%29%20%2A%20%28%28x%20-%203%29%28x%20-%203%29%2B1%29)
![P(x) = (x - 4) * (x^2 - 6x + 9+1)](https://tex.z-dn.net/?f=P%28x%29%20%3D%20%20%28x%20-%204%29%20%2A%20%28x%5E2%20-%206x%20%2B%209%2B1%29)
![P(x) = (x - 4) * (x^2 - 6x +10)](https://tex.z-dn.net/?f=P%28x%29%20%3D%20%20%28x%20-%204%29%20%2A%20%28x%5E2%20-%206x%20%2B10%29)
Open bracket
![P(x) = x^3 - 6x^2 +10x - 4x^2 + 24x-40](https://tex.z-dn.net/?f=P%28x%29%20%3D%20x%5E3%20-%206x%5E2%20%2B10x%20-%204x%5E2%20%2B%2024x-40)
![P(x) = x^3 - 6x^2 - 4x^2+10x + 24x-40](https://tex.z-dn.net/?f=P%28x%29%20%3D%20x%5E3%20-%206x%5E2%20%20-%204x%5E2%2B10x%20%2B%2024x-40)
![P(x) = x^3 - 10x^2+ 34x-40](https://tex.z-dn.net/?f=P%28x%29%20%3D%20x%5E3%20-%2010x%5E2%2B%2034x-40)